Effect of BCAA supplement timing on exercise-induced muscle soreness and damage: A pilot placebo-controlled double-blind study - Ra, S.-G.; Miyazaki, T.; Kojima, R.; Komine, S.; Ishikura, K.; Kawanaka, K.; Honda, A.; Matsuzaki, Y.; Ohmori, H. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the present study was to compare the effects of branched-chain amino acid (BCAA) supplementation taken before or after exercise on delayed onset muscle soreness (DOMS) and exercise-induced muscle damage (EIMD). METHODS: Fifteen young men (aged 21.5±0.4 years) were given either BCAA (9.6 g·day-1) or placebo before and after exercise (and for 3 days prior to and following the exercise day) in three independent groups: the control group (placebo before and after exercise), the PRE group (BCAA before exercise and placebo after exercise), and the POST group (placebo before exercise and BCAA after exercise). Participants performed 30 repetitions of eccentric exercise with the non-dominant arm. DOMS, upper arm circumference (CIR), elbow range of motion (ROM), serum creatine kinase (CK), lactate dehydrogenase (LDH), and aldolase, BCAA, and ß-hydroxy-ß-methylbutyrate (3HMB) were measured immediately before and after the exercise and on the following 4 days. RESULTS: Serum BCAA and 3HMB concentrations increased significantly in the PRE group immediately after the exercise, recovering to baseline over the following days. In the days following the exercise day, DOMS, CIR, and ROM were significantly improved in the PRE group compared to the control group, with weaker effects in the POST group. Serum activities of CK, LDH, and aldolase in the days following the exercise day were significantly suppressed in the PRE group compared to control group. CONCLUSIONS: The present study confirmed that repeated BCAA supplementation before exercise had a more beneficial effect in attenuating DOMS and EIMD induced by eccentric exercise than repeated supplementation after exercise.